A Multifunctional Nanocomposite Hydrogel for Endoscopic Tracking and Manipulation. (29th December 2019) - Augurio, Adriana; Cortelletti, Paolo; Tognato, Riccardo; Rios, Anne; Levato, Riccardo; Malda, Jos; Alini, Mauro; Eglin, David; Giancane, Gabriele; Speghini, Adolfo; Serra, Tiziano
Abstract : Herein, the fabrication of multi‐responsive and hierarchically organized nanomaterial using core‐shell SrF2 upconverting nanoparticles, doped with Yb 3+, Tm 3+, Nd 3+ incorporated into gelatin methacryloyl matrix, is reported. Upon 800 nm excitation, deep monitoring of 3D‐printed constructs is demonstrated. Addition of magnetic self‐assembly of iron oxide nanoparticles within the hydrogel provides anisotropic structuration from the nano‐ to the macro‐scale and magnetic responsiveness permitting remote manipulation. The present study provides a new strategy for the fabrication of a novel highly organized multi‐responsive material using additive manufacturing, which can have important implications in biomedicine. Abstract : Herein, the fabrication of a 3D‐printed multi‐responsive and hierarchically organized material doped with core‐shell upconverting nanoparticles and iron oxide nanoparticles is reported. The upconversion emission, generated by 800 nm excitation source, consents deep monitoring, whereas the magnetic self‐assembly allows remote manipulation of nanocomposite hydrogel. This light and magnetic field responsive hydrogel holds promise for generation of advanced bionic devices.